Antimycobacterial Activity of Hedeoma drummondii against Mycobacterium tuberculosis and Non-Tuberculous Mycobacteria - Molina Torres, Carmen Amelia; Pedraza Rodríguez, Carlos; Vera Cabrera, Lucio; Ocampo Candiani, Jorge; Rivas Morales, Catalina; Viveros Valdez, Ezequiel (Molecular Diversity Preservation International, 2023)
Tuberculosis (TB) remains a major health problem worldwide, and the emergence of multi-resistant strains to first-line drugs has become the biggest obstacle to its treatment. On the other hand, the incidence of non-tuberculous mycobacteria (NTM) in humans has increased remarkably in recent years. The search for new and better treatments against mycobacterial infections is a constant at the global level. Hence, in this study, we propose to investigate the antimycobacterial effect of the extracts and major compounds of Hedeoma drummondii against clinical isolates of Mycobacterium tuberculosis and non-tuberculous mycobacteria: M. abscessus, M. fortuitum, M. intracellulare, and M. gordonae. To determine the antimycobacterial activity, a microdilution assay was used to establish the minimum inhibitory concentration (MIC) of the different strains of Mycobacterium. The methanolic extract presented the best activity against M. tuberculosis, inhibiting ten of the twelve strains analyzed at a concentration < 2500 µg/mL; meanwhile, the hexanic extract presented the best activity against non-tuberculous mycobacteria (NTM) by inhibiting eight of the ten strains studied at ≤625 µg/mL. Moreover, there is a strong positive correlation between the antimycobacterial activity of pulegone and the hexanic extract against non-tuberculous strains, so this compound could serve as a predictability marker against these types of microorganisms.